FINANCIAL PERFORMANCE AND THEIR EFFECTS ON BASIC MATERIAL COMPANIES IN INDONESIA - Azhari, Erika; Eksandy, Arry; Wisdom, Epekele (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
In the current situation of the globalization era, business competition is becoming increasingly fierce, which makes every firm motivated to take advantage of its potential. This study aims to explain the effect of Firm Age, Institutional Ownership, and Managerial Ownership on the firm's Financial Performance. The sample used in this study is basic material sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The type of data used is secondary data obtained from www.idx.co.id. Samples were taken by purposive sampling method. The method used to analyze this research is panel data analysis method. Firm Age has no effect on the firm's Financial Performance. Institutional Ownership and Managerial Ownership affects the firm's Financial Performance.